Estimation of stability derivatives of a wedges at supersonic Mach numbers - Shanbhag, Pavithra; Lavanya, S; Khan, Sher Afghan (Institute of Institutional Industrial Research, 2017)
The present study aims at to determine the stability derivatives of a wedge in pitch with attached shock at different angle of attack in supersonic flow. The stability is obtained for a wedge by using the concept of a piston moving in a cylinder at any arbitrary speed, which is dependent on the Mach number and the wedge semi vertex angle. From the results it is seen that as the semi-vertex angle of the wedge increases, the Stiffness derivative increases linearly and damping derivative first decreases, attains a minima and then increases linearly which results due to the change in pressure field and varying position of center of pressure from leading edge of the wedge. Also as Mach number increases, both Stiffness derivatives and damping derivatives assumes lower values at nose of the wedge. Real gas effects, viscous effects, bluntness of leading edge, and secondary wave effects have not been considered in the present study.